Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme